Do Perceived Communication Behavior and International Posture Impact Iranian English Learners’ Communication in English? - Mehdi Sarkhosh (Applied Research on English Language, 2018)
Many studies have been conducted on the ways of promoting willingness to communicate in learners in EFL/ESL contexts. While different scholars have undertaken studies on many of these variables, few of these studies have aimed at EFL university students in Iran. This study reports on the role of international posture and perceived communication behavior on Iranian EFL learners’ communication in English. The participants who accepted to attend the survey completed questionnaires on WTC, international posture and perceived communication behaviors. The results driven based on this research indicated that Iranian English BA students are generally tended to speak in English. The participants' willingness to communicate in English was found to have a significant relationship with their perceived communication behaviors and international posture. The findings of this study will be beneficial for various policy makers and practitioners, including those dealing with curriculum development and teacher education to focus more on the elements influencing communication in English. Many studies have been conducted on the ways of promoting willingness to communicate in learners in EFL/ESL contexts. While different scholars have undertaken studies on many of these variables, few of these studies have aimed at EFL university students in Iran. This study reports on the role of international posture and perceived communication behavior on Iranian EFL learners’ communication in English. The participants who accepted to attend the survey completed questionnaires on WTC, international posture and perceived communication behaviors. The results driven based on this research indicated that Iranian English BA students are generally tended to speak in English. The participants' willingness to communicate in English was found to have a significant relationship with their perceived communication behaviors and international posture. The findings of this study will be beneficial for various policy makers and practitioners, including those dealing with curriculum development and teacher education to focus more on the elements influencing communication in English.